2005
DOI: 10.1152/japplphysiol.00412.2005
|View full text |Cite
|
Sign up to set email alerts
|

Thiol supplementation in aged animals alters antioxidant enzyme activity after heat stress

Abstract: Declines in oxidative and thermal stress tolerance are well documented in aging systems. It is thought that these alterations are due in part to reductions in antioxidant defenses. Although intracellular thiols are major redox buffers, their role in maintaining redox homeostasis is not completely understood, particularly during aging, where the reliance on antioxidant enzymes and proteins may be altered. To determine whether thiol supplementation improved the antioxidant enzyme profile of aged animals after he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Although intracellular thiols are major redox buffers, their role in maintaining redox homeostasis is not completely understood, particularly during aging. NAC treatment has a role not only in GSH activity, but in increased catalase and mitochondrial manganese superoxide dismutase activities [16]. NAC has an immunologic modulator role and not an indiscriminate stimulating effect.…”
Section: Discussionmentioning
confidence: 93%
“…Although intracellular thiols are major redox buffers, their role in maintaining redox homeostasis is not completely understood, particularly during aging. NAC treatment has a role not only in GSH activity, but in increased catalase and mitochondrial manganese superoxide dismutase activities [16]. NAC has an immunologic modulator role and not an indiscriminate stimulating effect.…”
Section: Discussionmentioning
confidence: 93%
“…In phase 2 of the study, a subset of animals ( n = 24) receiving combined RF ablation and liposomal doxorubicin therapy was used to examine the outcomes of blocking the effects of cellular stress. N -acetylcysteine (NAC) (American Regent, Shirley, NY), a thiol antioxidant ( 35 ), was administered at a dose of 300 mg per kilogram of body weight by using intraperitoneal injection ( n = 12) at 24 hours and 1 hour prior to RF application. Tissues were harvested at 30 minutes, 60 minutes, and 4 hours after ablation (four animals at each time point) and examined for evidence of 8-OHdG, NT, and cleaved caspase-3.…”
Section: Liposomal Doxorubicin Administrationmentioning
confidence: 99%
“…This indicates that the antioxidant enzyme is not destroyed during the acute heat stress. This indication is also proved by a rat study, which found the enzyme activity and the severity affected by additional exposure to acute stresses depend on the affected brain region and the type of stress (Morrison et al, 2005;Pejić et al, 2006). The immobilization stress increases the CuZnSOD activity in the hippocampus and the cortex while the cold stress decreases its activity in these regions.…”
Section: Discussionmentioning
confidence: 71%